KAJIAN REAKTIVASI JALAN REL DI TERMINAL PETI KEMAS SEMARANG - Pratiwi, Arlisa; Ningrum, Inovia Cahya; Kushardjoko, Wahyudi; Indriastuti, Amelia Kusuma (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Along with increasing amount of using container as distribution of goods, Central Java Provincial Government with PT. KAI and PT. Pelindo III planned reactivation of railway to distribute freight container. This meant that distribution of container on highway can be reduced, so the density and number of traffic accidents also the use of fuel can be reduced. The study aims to identify the traffic of containers, determine the origin-destination, cargo and container tonnage, predict future container needs, and design the railway construction. Methods of analysis were GDP data processing using shift share analysis and container demand prediction using regression analysis. Railway construction planning refers to PD no.10/1986 and other applicable guidelines. The result showed that container traffic at Semarang Container Terminal is constantly increasing. In 2013, the amount of movement of export-import reached 524.139TEUs, divided into 3 regions of origin/destination, western (24.43%), southern (53.23%) and eastern (22.34%). From the results of shift share analysis and regression, it is predicted that 30years later, container demand will reach 47.254.973Ton/Year. With such loads, the railroad is classified into first class, with maximum speed 60km/h, using R.54 types with 250m length, connected by bolts and welding, fastened by double elastic Pandrol type, and using prestressed concrete pads. Sub-ballast thickness needed is 20cm. Railway crossing is accomodated using wessel no.10.